TEKNIK PEMBESARAN KEPITING BAKAU (SCYLLA SP.) DENGAN SISTEM APARTEMEN - OLIVIA NINGSIH; RANGGA IDRIS AFFANDI (Universitas Mahasaraswati K. Mataram, 2023)
Mud crab or known as Scylla sp. is one of the coastal resources that has economic value and contains high nutrition. This causes the market demand for mud crabs is continue to increase from time to time. So, it is necessary to do mud crab cultivation. One strategy for managing crab cultivation can be done through an apartment system. This vertical aquaculture technology is the third evolution in mud crab cultivation after cultivation in nature and horizontal system cultivation which is generally carried out using ponds. Based on this, this study aims to determine the method of enlargement mud crabs with the apartment system. This research activity was carried out in March-April 2023 at the Brackish Water Aquaculture Center (BBPBAP) Jepara, Central Java. Data collection techniques used in this research are descriptive methods and field observations. The results obtained are knowing the stages of mud crab enlargement activities with the apartment system including preparation of rearing containers, crab selection, crab stocking, feed management, water quality management, harvesting, packaging, and transportation. The highest weight growth during the study was 372 g in Apartment 1 Floor 5. The highest Survival Rate (SR) value during the study was obtained from stocking 14 mud crabs per floor was 57% in Apartment 1 Floor 6. The value of water quality parameters during the study included temperature, pH, DO, and salinity are good and support for the life of mud crabs.